Development of the channel type centrifugal pump - A. P. Kuleshov; G. P. Itkin; A. S. Baybikov (Вестник трансплантологии и искусственных органов, 2018)
A channel centrifugal pump has been developed which have calculated parameters during the nominal operating mode based on 3-dimensional computer simulation  (flow rate 5 l/min, pressure drop 100 mm). In addition, pump’s operating conditions in ECMO mode are considered at high pressure drops of 200–300 mm Hg with a  speed of rotor up to 3500 rpm. Simulation result was a creation of a new channel- type centrifugal pump with shear stress that do not exceed the allowable threshold  of 150 Pa, and also minimizing stagnation and flow recirculation zones. The  obtained data were also the result of use design of rotor with constant cross-section channels formed along a logarithmic curve and ensuring minimum turbulence due to the minimum outlet angle of the flow.